Concerted regulation of non-alcoholic fatty liver disease progression by microRNAs in apolipoprotein E-deficient mice - Andrea R. López-Pastor; Jorge Infante-Menéndez; Tamara González-Illanes; Paula González-López; Águeda González-Rodríguez; Carmelo García-Monzón; Melina Vega de Céniga; Leticia Esparza; Almudena Gómez-Hernández; Óscar Escribano (The Company of Biologists, 2021)
The prevalence of non-alcoholic fatty liver disease (NAFLD) is constantly increasing, and altered expression of microRNAs (miRNAs) fosters the development and progression of many pathologies, including NAFLD. Therefore, we explored the role of new miRNAs involved in the molecular mechanisms that trigger NAFLD progression and evaluated them as biomarkers for diagnosis. As a NAFLD model, we used apolipoprotein E-deficient mice administered a high-fat diet for 8 or 18 weeks. We demonstrated that insulin resistance and decreased lipogenesis and autophagy observed after 18 weeks on the diet are related to a concerted regulation carried out by miR-26b-5p, miR-34a-5p, miR-149-5p and miR-375-3p. We also propose circulating let-7d-5p and miR-146b-5p as potential biomarkers of early stages of NAFLD. Finally, we confirmed that circulating miR-34a-5p and miR-375-3p are elevated in the late stages of NAFLD and that miR-27b-3p and miR-122-5p are increased with disease progression. Our results reveal a synergistic regulation of key processes in NAFLD development and progression by miRNAs. Further investigation is needed to unravel the roles of these miRNAs for developing new strategies for NAFLD treatment. This article has an associated First Person interview with the joint first authors of the paper.